2009
DOI: 10.1115/1.4000416
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Mask Image Projection for Solid Freeform Fabrication

Abstract: Solid freeform fabrication (SFF) processes based on mask image projection have the potential to be fast and inexpensive. More and more research and commercial systems have been developed based on these processes. For the SFF processes, the mask image planning is an important process planning step. In this paper, we present an optimization based method for mask image planning. It is based on a light intensity blending technique called pixel blending. By intelligently controlling pixels’ gray scale values, the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…First, consider the prior for the total equivalent amounts. We observed from the work of Zhou, Chen, and Waltz [35] and Zhou and Chen [34] that a product's size should not impact the spread of light beams on its boundary, and that this impact in terms of the equivalent amount of compensation should be relatively small (in inches). These observations led to our bounds 0 ≤ T i,2 (0, x 2 (·)) ≤ 0.015 for all points, with the upper bound not depending on the nominal radius of the cylinder on which a point resides.…”
Section: 2mentioning
confidence: 99%
“…First, consider the prior for the total equivalent amounts. We observed from the work of Zhou, Chen, and Waltz [35] and Zhou and Chen [34] that a product's size should not impact the spread of light beams on its boundary, and that this impact in terms of the equivalent amount of compensation should be relatively small (in inches). These observations led to our bounds 0 ≤ T i,2 (0, x 2 (·)) ≤ 0.015 for all points, with the upper bound not depending on the nominal radius of the cylinder on which a point resides.…”
Section: 2mentioning
confidence: 99%
“…For most contributions, optimisation in AM is classically considered as a process parameter optimisation as it is the case for many design techniques [77,78]. Raster angle, building direction, layer dimensions are some of the main parameters that find some interest in the literature.…”
Section: Optimisation In Additive Manufacturingmentioning
confidence: 99%
“…Accurate dimension, acceptable roughness and processing time are some of the important outcomes that justify the continuity of the research effort in this particular field. A typical example showing the importance of the process optimisation is provided in recent works [54,55,78]. The paper by Zhou et al [78] introduces the concept of pixel blending to define the effect of neighbour pixels light intensity in solid freeform fabrication using photopolymerisation medium.…”
Section: Optimisation In Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of works [5,6,7] has shown that the accuracy of the SLA models is most affected by positioning, thickness of the layer, type of post-processing, and by the prototypes design features. When the critical parts of the model are positioned at the angle of 45 degrees, and thickness of the build layer is reduced, the form error decreases, and the quality of the surface improves.…”
Section: Introductionmentioning
confidence: 99%